Training on Making Lamb Meat Nuggets with the Addition of Moringa Leaves (Moringa Leifra) - Asmaq, Nur; Warsito, Kabul; Matondang, Syaiful Nasri; Suhut, Anwar (East Asian Journal of Multidisciplinary Research, 2023)
Livestock products are products that have high nutritional value, namely protein, fat, water and micromolecules. One of the livestock products consumed by the public is meat. Meat tends to have a very short time in storage, namely only 1-3 hours before it spoils or becomes contaminated with bacteria. Bacterial contamination is very dangerous for consumers because it can cause several diseases such as diarrhea. Processed livestock products such as nuggets can be preserved using natural ingredients, one of which is Moringa leifra leaves. This plant contains antimicrobial and antioxidant properties which can maintain the quality of the product to remain good or at least extend the life of the product. This horticultural plant is very well known by the public, especially mothers and women who like to cook. Usually, this plant is used as a vegetable. The people in Bulu Cina Village are breeders who sell live, unprocessed sheep. Farmers do not yet know how to develop livestock businesses, such as opening catering or businesses that process sheep meat such as nuggets. Increasing public knowledge about preserving meat nuggets using Moringa leaves is very much needed in order to extend and maintain good product quality, especially microorganisms. This activity can be given to women, both teenagers, adults and housewives who are members of the PKK or not.